Can the Cardiopulmonary 6-Minute Walk Test Reproduce the Usual Activities of Patients with Heart Failure? - Guimarães,Guilherme Veiga (2002)
OBJECTIVE: The 6-minute walk test is an way of assessing exercise capacity and predicting survival in heart failure. The 6-minute walk test was suggested to be similar to that of daily activities. We investigated the effect of motivation during the 6-minute walk test in heart failure. METHODS: We studied 12 males, age 45±12 years, ejection fraction 23±7%, and functional class III. Patients underwent the following tests: maximal cardiopulmonary exercise test on the treadmill (max), cardiopulmonary 6-minute walk test with the walking rhythm maintained between relatively easy and slightly tiring (levels 11 and 13 on the Borg scale) (6EB), and cardiopulmonary 6-minute walk test using the usual recommendations (6RU). The 6EB and 6RU tests were performed on a treadmill with zero inclination and control of the velocity by the patient. RESULTS: The values obtained in the max, 6EB, and 6RU tests were, respectively, as follows: O2 consumption (ml.kg-1.min-1) 15.4±1.8, 9.8±1.9 (60±10%), and 13.3±2.2 (90±10%); heart rate (bpm) 142±12, 110±13 (77±9%), and 126±11 (89±7%); distance walked (m) 733±147, 332±66, and 470±48; and respiratory exchange ratio (R) 1.13±0.06, 0.9±0.06, and 1.06±0.12. Significant differences were observed in the values of the variables cited between the max and 6EB tests, the max and 6RU tests, and the 6EB and 6RU tests (p<0.05). CONCLUSION: Patients, who undergo the cardiopulmonary 6-minute walk test and are motivated to walk as much as they possibly can, usually walk almost to their maximum capacity, which may not correspond to that of their daily activities. The use of the Borg scale during the cardiopulmonary 6-minute walk test seems to better correspond to the metabolic demand of the usual activities in this group of patients.